External focus facilitates cognitive stability and promotes motor performance of an interceptive task in children. - Abdollahipour, Reza; Land, William M.; Valtr, Ludvík; Banátová, Kamila; Janura, Miroslav (International Journal of Sport & Exercise Psychology, 2023)
Recent evidence suggests that one of the benefits of external focus is facilitating task focus. To this extent, an external focus might influence cognitive function. To help elucidate the underlying mechanisms of attentional focus instructions, the aim of this study was to examine the influence of attentional focus instructions on cognitive stability and task focus, as indicated by the number of eye blinks, during an interceptive timing task with children who are at a crucial stage of motor coordination development. Twenty-four children (M = 10.4 ± 0.9 years) performed a forehand drag shot with a floorball stick to hit a tennis ball at a target in each of three different attentional focus conditions: external focus "focus on the blade of the stick", internal focus "focus on their hands", and control (no focus instructions). A mobile eye tracker was used to record the number of eye blinks from the moment that the tennis ball was released by an experimenter from the top of a boccia ramp to the moment of the initial movement of the floorball stick. Results showed that the accuracy of hits was significantly better in the external focus relative to the internal focus condition. Also, the number of eye blinks was significantly lower in the external focus relative to the internal focus and control conditions. Findings suggest that improved cognitive stability and task focus may underlie the improved performance associated with an external focus in a visually demanding motor task in children.